2009
DOI: 10.1016/j.jsb.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin position in human HepG2 cells: Although being non-random, significantly changed in daughter cells

Abstract: Mammalian chromosomes occupy chromosome territories within nuclear space the positions of which are generally accepted as non-random. However, it is still controversial whether position of chromosome territories/chromatin is maintained in daughter cells. We addressed this issue and investigated maintenance of various chromatin regions of unknown composition as well as nucleolus-associated chromatin, a significant part of which is composed of nucleolus organizer region-bearing chromosomes. The photoconvertible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
(62 reference statements)
8
19
0
Order By: Relevance
“…6F, lower). In line with previous studies, 14,16 however, this finding argues against a complete randomization of CT proximity patterns present in the mother nucleus already after a single mitotic event. In such a case we would have expected scattering of fluorescent chromatin patches throughout the entire nuclear space in all experiments where we activated paGFP-H4 in a half or a quarter of the nuclear area.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…6F, lower). In line with previous studies, 14,16 however, this finding argues against a complete randomization of CT proximity patterns present in the mother nucleus already after a single mitotic event. In such a case we would have expected scattering of fluorescent chromatin patches throughout the entire nuclear space in all experiments where we activated paGFP-H4 in a half or a quarter of the nuclear area.…”
Section: Resultssupporting
confidence: 90%
“…Several groups have studied this problem in living cells taking advantage of cell lines, which express core histones tagged with fluorescent proteins. [14][15][16] Lasermicroirradiation was used to produce fluorescent chromatin patterns, which were then followed through interphase and mitosis. Gerlich et al 15 concluded that global chromosome positions are maintained in cycling mammalian cells and proposed a mechanism acting at anaphase to restore the loss of order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed following up fluorescently labeled chromatin through mitosis into the next interphase. Present evidence argues for the stability of a given CT neighborhood arrangement once established at the onset of interphase until the next prophase, whereas chromosome movements during prometaphase necessary to establish the metaphase plate can lead to major changes of side-by-side chromosome arrangements in the metaphase plate compared with the side-by-side arrangements of the respective CTs during the preceding interphase (Walter et al 2003;Cvackova et al 2009). …”
Section: Stability and Changes Of Ct Arrangements In Cycling Cellsmentioning
confidence: 84%
“…The subsequent cultivation of these cells for three or more additional cell cycles resulted in the formation of nuclei with a few in vivo-labeled CTs that were separated by nonlabeled CTs [34][35][36][37]. Eventually, tests of Boveri's hypotheses II-IV in living cells became possible using cell lines that expressed core histones tagged with fluorescent proteins [8, 36,38]. In this way, by using laser microirradiation, distinct fluorescent chromatin patterns could be established in interphase nuclei or on mitotic chromosomes, and tracked through interphase and mitosis.…”
Section: Chromosome Territories: An Early Concept and Its Late Experimentioning
confidence: 99%